Hypothesis for heritable, anti-viral immunity in crustaceans and insects - Flegel, Timothy W (BioMed Central, 2009)
Correction to Flegel, TW: Hypothesis for heritable, anti-viral immunity in crustaceans and insects. Biology Direct 2009, 4:32.